Design and Build a Website-Based Waste Alms Management Information System Using the Laravel Framework (Case Study of KSM Jameela Brang Biji Sumbawa) - Yudi Mulyanto; Eri Sasmita Susanto; Arzikman; I Made Widiarta; Fahri Hamdani (Journal of Applied Informatics Science, 2026)
Waste management remains a crucial issue in various regions, including Sumbawa. KSM Jameela Brang Biji took the initiative to manage waste through a garbage alms program. However, the processes of recording, managing donor data, and reporting are still conducted manually, making them prone to errors, lacking transparency, and highly inefficient. Therefore, this research aims to design and build a website-based Garbage Alms Management Information System using the Laravel framework to facilitate KSM Jameela's operations. The software development applies the Agile Scrum method, which allows for quick iterations and adaptation to user needs. This system was built using the PHP programming language and a MySQL database. Software quality testing was conducted using the Black Box method to ensure all feature functionalities operate according to specifications, and the White Box method to evaluate the internal logical structure of the code. The research results indicate that the developed system successfully digitalizes the garbage alms management process, ranging from donor registration and waste transaction recording to real-time report generation. In conclusion, the implementation of this system is proven to significantly improve operational efficiency, data accuracy, and management transparency, thereby supporting KSM Jameela in optimizing the garbage alms program and encouraging broader community participation.